Beneficial Effects of Dates (Phoenix Dactylifera) and Goat Milk in Iron Deficiency Anaemia - Noor Fadzilah Zulkifli; Nazefah Abdul Hamid; Nuruliza Roslan; Nurul Nadiah Mad Zahir; Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Nur Syahrina Binti Rahim; Nor Aripin Shamaan (Academy of Medicine of Malaysia, 2024)
The International Congress of Pathology & Laboratory Medicine 2018: Frontiers in Diagnostic Pathology, organised by the College of Pathologists, Academy of Medicine of Malaysia and was held at Connexion Conference & Event Centre – The Vertical at Bangsar South on 28-30 June 2018.